A simple procedure for retrieval of a cement-retained implant-supported crown: a case report - Buzayan, M.M.; Mahmood, W.A.A.; Yunus, N. (Quintessence Publishing, 2014)
Retrieval of cement-retained implant prostheses can be more demanding than retrieval of screw-retained prostheses. This case report describes a simple and predictable procedure to locate the abutment screw access openings of cementretained implant-supported crowns in cases of fractured ceramic veneer. A conventional periapical radiography image was captured using a digital camera, transferred to a computer, and manipulated using Microsoft Word document software to estimate the location of the abutment screw access.